EFFECT OF FORUM SELECTION CLAUSES IN INVESTMENT ARBITRATION - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2019)
The conclusion of contracts between investors and host States is a common feature in international investment law. In many disputes, such investment agreements play a major role. The existence of such contractual agreements and the claims arising in the investment disputes surrounding them, have given rise to a plethora of legal issues, which will be addressed in this contribution. Initially, it is necessary to distinguish between breaches of a treaty and breaches of contract. Not every breach of a contract by a State amounts to a breach of international law. There is a large body of case law setting out the line at which a breach of contract under domestic law amounts also to a breach of international law. This can either be due to the specific circumstances of the breach or to the existence of an umbrella clause. Cases involving breaches of contract invariably also have given rise to complex disputes about the jurisdiction of the treaty-based tribunal deciding on them. The main questions have focused on whether such tribunals can hear claims based on the breach of a contract as a preliminary question to determining a breach of a treaty, the jurisdiction of treaty-based tribunals to hear claims for the breach of contracts not amounting to breaches of international law and the relevance of contractually agreed dispute resolution provisions. None of the above questions have yet produced uniform answers. There are, however, certain approaches depending whether the applicable investment treaty provide for an “umbrella clause”, or the investment treaty has a limited rationae materie scope of protection. These aspects will be discussed in this article. Keywords: investment protection, contract claims, observance of investment undertakings, investment arbitration, scope of protection.